Synthesis of highly stable κ/ι-hybrid carrageenan micro- and nanogels via a sonication-assisted microemulsion route - Rodriguez S. (2020)
The authors disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This work was supported by the National Council of Science, Technology and Technological Innovation [CONCYTEC-FONDECYT]; and the Vice-Rectorate for Research of the Pontificia Universidad Catolica del Peru [VRI-PUCP].